Applied ethnomusicology and empowerment strategies - Pettan, Svanibor (Muzikološki zbornik, 2008)
The article consists of three parts. The first part presents an outline of the historical developments of applied ethnomusicology in Europe and USA, from the public sector activities of comparative musicologists in the early 20th c. all the way to the announcement of the first conference of newly-established ICTM's study group in Ljubljana in 2008. The second part is dedicated to the issues of definition and classification of approaches. The third part features five categories of subjects (minorities, diasporas, ethnic groups, immigrants, refugees) and based on selected examples from the territories of what was Yugoslavia presents ethnomusicological interventions that exceed the obvious academic goals of broadening and deepening of scholarly knowledge.
Keywords: aplikativna etnomuzikologija; begunci; diaspore; etnične skupine; manjšine